Correction: Study of structures and thermodynamics of CuNi nanoalloys using a new DFT-fitted atomistic potential. Issue 42 (19th June 2015) - Panizon, Emanuele; Olmos-Asar, Jimena A.; Peressi, Maria; Ferrando, Riccardo
Abstract : Correction for 'Study of structures and thermodynamics of CuNi nanoalloys using a new DFT-fitted atomistic potential' by Emanuele Panizon et al., Phys. Chem. Chem. Phys., 2015, DOI: ; Web:10.1039/c5cp00215j .